The Analysis of Code Switching in the Novel "Critical Eleven" by Ika Natasha - Larasani, Gusti Putu; Sadia, I Gede (Humanis; Vol 23 No 2 (2019), 2019)
The undergraduate thesis is entitled “The Analysis of Code Switching in the Novel “Critical Eleven” By Ika Natasha”. The aim of this study is to analyze type and function of code switching in the novel. The novel entitled “Critical Eleven” was chosen because this novel is a great novel and the dialogues use many code switchings. There are two problems to be investigated: First,  What types of code switching were found in this novel? And the second one What kinds of function of code switching were applied in this novel? The method used in collecting data was the documentation method and the data were analyzed using the theory proposed by Muysken in “The Cambridge Handbook of Sociolinguistics”. The result of this study shows that there were seventeen examples of tag switching, twenty four examples of inter sentential switching and fifty six examples of intra sentential switching. There were six examples of emotive function, two examples referential function, four examples of phatic function, five examples of metalinguistic function and only one example of poetic function but the conative function was not found.